Communication Of The Crisis Of Hotel Ibis Budget Daan Mogot Jakarta In Facing The Covid-19 Pandemic - Deny Hendriyatmoko; Marlinda Irwanti Poernomo (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to understand the crisis response strategy that occurred at the Ibis Daan Mogot Hotel Jakarta in dealing with the Covid-19 pandemic. The research method used is case study research with a descriptive approach with qualitative data types. Researchers use a post-positivism paradigm because researchers want to build understanding regarding the crisis communication strategy of the Ibis Budget Daan Mogot Hotel Jakarta in dealing with the Covid-19 pandemic. The post-positivism paradigm trusts more in the process of verifying a finding of results using various methods so that researchers choose this paradigm. In this study the researcher is the key instrument, the data collection technique is carried out by triangulation or combination, the data analysis is inductive or qualitative, and the results of qualitative research emphasize meaning rather than generalization. In this study, Miles and Huberman's analytical techniques were used which consisted of data reduction, data presentation, and drawing conclusions. In this study the researchers explored the truth of the information through interviews with various parties. In addition, researchers also make observations, archives, and photographs, as well as observing news and websites. The crisis that occurred at the Ibis Budget Hotel Jakarta Daan Mogot Jakarta was a crisis caused by the Covid-19 pandemic so that the crisis that occurred could be categorized as a victim cluster type of crisis because it was caused by the Covid-19 pandemic. In the victim cluster, it means that the Ibis Budget Hotel Jakarta Daan Mogot Jakarta positions itself as a victim so that the attribution that the company is responsible for the crisis is very weak. This provides an advantage for the Ibis Budget Hotel Jakarta Daan Mogot Jakarta because the threat to reputation is relatively mild.